2007
DOI: 10.15560/3.2.100
|View full text |Cite
|
Sign up to set email alerts
|

Amphibia, Anura, Bufonidae, Melanophryniscus dorsalis: distribution extension in the State of Rio Grande do Sul, Brazil

Abstract: None

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Considerable new occurrence data were recorded for this study (Table S1), following the indicated areas in Figure S1. We also included the new record published by Quintela et al (2007), which extends the known distribution of M. dorsalis 285 kilometers to the south and was reconfirmed by this study (point 7) (see Table S1). Field expeditions were conducted to confirm species occurrence in points 6, 8 and 10 (M. dorsalis), with a successful rediscovery at point 6 and no success at points 8 and 10.…”
Section: Resultsmentioning
confidence: 83%
“…Considerable new occurrence data were recorded for this study (Table S1), following the indicated areas in Figure S1. We also included the new record published by Quintela et al (2007), which extends the known distribution of M. dorsalis 285 kilometers to the south and was reconfirmed by this study (point 7) (see Table S1). Field expeditions were conducted to confirm species occurrence in points 6, 8 and 10 (M. dorsalis), with a successful rediscovery at point 6 and no success at points 8 and 10.…”
Section: Resultsmentioning
confidence: 83%
“…Sampling efforts on anuran (Quintela et al 2007, Bernardo-Silva et al 2012, Dalmolin et al 2017, reptilian (Quintela et al 2011) and avian fauna (Gianuca et al 2007(Gianuca et al , 2008(Gianuca et al , 2012 in the insular environments have identified the occurrence of some unexpected taxa for the region, including the southernmost and isolated population of the threatened red-bellied toad Melanophryniscus dorsalis (Mertens, 1933) (Quintela et al 2006, Bernardo-Silva et al 2012. While some groups such as herpetofauna and avifauna are relatively well-known in the island, the ichthyofauna remained practically unexplored.…”
Section: Introductionmentioning
confidence: 99%